ISOLASI DAN IDENTIFIKASI BAKTERI PENDEGRADASI LIPID (LEMAK) PADA BEBERAPA TEMPAT PEMBUANGAN LIMBAH DAN ESTUARI DAM DENPASAR - I. B. G. Gede Darmayasa (Bumi Lestari Journal of Environment, 2008)
Research on isolation and identification of lipid degrading bacteria in some sewage disposing sites and Denpasar Estuary Dam was carried out in April, 2006. This research aims to identify fat degrading bacteria on those areas.Isolation of bacteria was undertaken using thinning methods (platting methods) grown at sierra media. Colonies observed on the media after incubation on the temperature of 30-370C for 24 hours were identified based on macroscopic observations, biochemical tests, microscopic and cross tests to ensure that the bacteria identified was absolutely lipid degrading bacteria.The research result showed that number of lipid degrading bacteria isolates obtained from three sampling sites were 7 isolates. Four isolates were obtained from samples taken on BTDC Lagoons, the samples of which contains Bacillus sp. (A). Bacillus sp. (B), Klebsiella sp. and Staphylococcus sp., 2 isolates were gotten from samples found in estuary DAM with bacteria of Bacillus sp. (A) and Klebsiella sp. and 1 isolate was gotten from slaughterhouse waste disposal with Klebsiella sp. bacteria. Cross test results carried out on the seven isolates showed that two genera of bacteria only, namely: Bacillus sp. and Pseudomonas sp., which were viable after inoculation and 24 hours of incubation time.